2020
DOI: 10.1186/s12911-020-01294-9
|View full text |Cite
|
Sign up to set email alerts
|

The multi-faceted usage patterns of nutrition apps: a survey on the appropriation of nutrition apps among German-speaking users of MyFitnessPal

Abstract: Background Current systematic reviews of randomized controlled trials suggest positive influences of mobile app-based health promotion programs on dietary and physical activity behaviors. However, the actual adoption of and rates of nutrition app use remain low among the overall population. Therefore, we took a step back and investigated actual use patterns. In doing so, we took an appropriation perspective in order to reveal different styles of everyday life integration of these apps. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…According to Stehr et al (2020), research on nutrition apps thus far has concentrated on evaluating their effectiveness, which has led to variable results [13]. While a change towards increased diet quality or attainment of diet-related goals is positive, there is concern that mobile applications and their use in dietary health can promote negative dietary habits; an overdependence on the application may affect the long-term benefits to the user [14].…”
Section: Introductionmentioning
confidence: 99%
“…According to Stehr et al (2020), research on nutrition apps thus far has concentrated on evaluating their effectiveness, which has led to variable results [13]. While a change towards increased diet quality or attainment of diet-related goals is positive, there is concern that mobile applications and their use in dietary health can promote negative dietary habits; an overdependence on the application may affect the long-term benefits to the user [14].…”
Section: Introductionmentioning
confidence: 99%
“…Another important limitation is that we did not consider factors that motivated users to continue using PA apps in our analyses. Research has shown that the retention rate of commercial health care apps is extremely low [48], and different users have different motivations to maintain the use of an app [49,50], such as adjusting default settings to one's own needs and abilities, socializing, and competition. Additionally, it is important to consider users' willingness to share their data from mHealth tools with providers as well as peers and family, which is key when implementing mHealth services as a meaningful intervention [51,52].…”
Section: Limitationsmentioning
confidence: 99%
“…Similar to any other software, P-DHI apps should be user-centered and tailored to the context [22,26,40,42,46,[67][68][69][70][71][72][73][74][75][76][77].…”
Section: P-dhis: It Investmentmentioning
confidence: 99%